Computer-Assessed Preference-Based Quality of Life in Patients with Spinal Cord Injury. (30th August 2017) - Parimbelli, Enea; Pistarini, Caterina; Fizzotti, Gabriella; Rognoni, Carla; Olivieri, Giampiero; Quaglini, Silvana
Abstract : Objectives . Our aims were to (1) measure quality of life (QoL) in spinal cord injury (SCI) patients using different methods and analyze differences; (2) enable targeted treatments by identifying variables that affect QoL; and (3) provide decision-makers with useful data for cost-utility analyses in SCI population. Methods . Seventy-one participants were enrolled. The computer-based tool UceWeb was used to elicit QoL in terms of utility coefficients, through the standard gamble, time trade-off, and rating scale methods. The SF36 questionnaire was also administered. Statistical analyses were performed to find predictors of QoL among collected variables. Results . Median values for rating scale, time trade-off, and standard gamble were 0.60, 0.82, and 0.85, respectively. All scales were significantly correlated. Rating scale and SF36 provided similar values, significantly lower than the other methods. Impairment level, male gender, older age, living alone, and higher education were correlated with lower QoL but accounted for only 20% of the variation in utility coefficients. Conclusions . Demographic and clinical variables are useful to predict QoL but do not completely capture utility coefficients variability. Therefore, direct preference-based utility elicitation should be strengthened. Finally, this is the first study providing data that can be used as a reference for cost-utility analyses in the Italian SCI population.